A Summary of Current Developments in the Processing of Agri-Food Using Digital Technologies - Ahlam Ahmed Skeep (المجلة الليبية للدراسات الأكاديمية المعاصرة, 2025)
Food Processing has undergone a qualitative transformation thanks to digital technology, as it has become a key tool for improving efficiency, reducing waste, and ensuring product quality, the need for these digital transformations is increasing to address global challenges, such as population growth, climate change, and the need for resource sustainability, the research results have proven that the application of digital technology in food manufacturing achieves benefits in terms of improving food quality and safety through sensor systems that monitor environmental conditions during production and storage, which reduces the risk of food contamination by up to 30% and reduces production losses thanks to artificial intelligence that analyzes operational data and identifies production stages that consume excessive amounts of water or raw materials, which contributes to reducing food waste and improving transparency in food supply chains through blockchain technology, which enhances consumer confidence by 15% in tracing the source of food products, and to personalize food products using 3D printing, which enables the production of customized foods with a balanced nutritional composition that meets the health needs of individuals, despite these benefits, the industry faces challenges, most notably the high costs of adopting digital technology, weak infrastructure in some rural areas, and lack of technical knowledge among the workforce.